The mazEF toxin-antitoxin system as a novel antibacterial target in Acinetobacter baumannii - Ghafourian, Sobhan; Good, Liam; Sekawi, Zamberi; Awang Hamat, Rukman; Soheili, Sara; Sadeghifard, Nourkhoda; Neela, Vasantha Kumari (Instituto Oswaldo Cruz, 2014)
Although analysis of toxin-antitoxin (TA) systems can be instructive, to date, there is no information on the prevalence and identity of TA systems based on a large panel of Acinetobacter baumannii clinical isolates. The aim of the current study was to screen for functional TA systems among clinical isolates of A. baumannii and to identify the systems' locations. For this purpose, we screened 85 A. baumannii isolates collected from different clinical sources for the presence of the mazEF, relBE and higBA TA genes. The results revealed that the genes coding for the mazEF TA system were commonly present in all clinical isolates of A. baumannii. Reverse transcriptase-polymerase chain reaction analysis showed that transcripts were produced in the clinical isolates. Our findings showed that TA genes are prevalent, harboured by chromosomes and transcribed within A. baumannii. Hence, activation of the toxin proteins in the mazEF TA system should be investigated further as an effective antibacterial strategy against this bacterium.